Purwarupa Pembangkit Listrik Tenaga Ombak Dengan Konsep Oscillating Water Coloumn (Skala Laboratorium) - Yeddid Yonatan Eka Darma; I.G.N.A Satria Prasetya D.Y; Heri Inprasetyobudi; Moh Nurpambudi Hidayat; Diky Nurwahyudi (Politeknik Negeri Padang, 2020)
Electricity energy demands for peoples near the sea are same high as people in the city, but sometimes electricity in coastal residence are nearly forgotten. In that case we need an alternative energy source for electricity generation using friendly environmental and renewable energy to maintain the availability of electrical energy. One of the energy alternative is sea wave power such as Oscillating Water Column (OWC) system. The Oscillating Water Column system have three main components, such as the chamber, air turbine (wells turbine) and generator. The chamber function is a place for oscillation between water and air, then the function of water turbine (wells turbine) is to capture energy (air flow) that will be used to rotate the generator, that producing electrical energy. This turbine is 22 cm in diameter and will use the NACA0012 airfoil. This research was conducted to design an oscillating water column on a laboratory scale. This research is expected to be the beginning of renewable energy development sources and as the alternative energy source for the community in Banyuwangi.